Cardiac involvement in systemic sclerosis: Getting to the heart of the matter. Issue 3 (September 2021) - Bruni, Cosimo; Ross, Laura
Abstract: Primary systemic sclerosis heart involvement (pSHI) is an important disease manifestation that accounts for a significant proportion of systemic sclerosis (SSc)-associated mortality. A broad clinical spectrum of pSHI exists, which ranges from asymptomatic perfusion abnormalities to diastolic dysfunction or acute myocarditis and congestive heart failure. With improving sensitivity of cardiac investigations, it is increasingly recognized that there is a large burden of subclinical cardiac disease in patients with SSc. Early signs of pSHI can be subtle and determining the etiology of cardiac abnormalities from other causes of cardiomyopathy such as hypertension, ischemic heart disease (IHD), and pulmonary vascular disease remain challenging. Early identification of pSHI potentially provides clinicians with a window of opportunity for intervention to avert progression to heart failure. However, optimal screening and treatment guidelines are lacking, and it is an area of much needed further clinical research.